2018
DOI: 10.1039/c7ra13269g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of 3D flower-like Pt nanostructures on polypyrrole nanowire matrix for enhanced methanol oxidation

Abstract: Platinum nanoflowers on polymer nanowires exhibit catalytic properties ascribed to the effect of high surface area flower-like structures and polymer 3D structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Creating micro-nano-roughness on the electrode surface and depositing nano-materials on the WE are some of the common strategies to enhance the ECSA of the WE. 18,19 Hsu et al roughened the Si substrate by etching silicon nanowires, which were then coated with gold for enzymatic glucose sensing. 20 Using this approach, the ECSA was 6.12 times higher as compared to planar gold electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Creating micro-nano-roughness on the electrode surface and depositing nano-materials on the WE are some of the common strategies to enhance the ECSA of the WE. 18,19 Hsu et al roughened the Si substrate by etching silicon nanowires, which were then coated with gold for enzymatic glucose sensing. 20 Using this approach, the ECSA was 6.12 times higher as compared to planar gold electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…3 Besides possessing high tolerance to CO and activity towards O-H and C-H bond cleavage, electrocatalysts designed for oxidizing alcohols with two or more carbon atoms (C2+) must also be able to efficiently cleave C-C bonds, which is necessary for complete conversion to CO2. 4 To address the CO poisoning issue, researchers have explored different catalyst geometries, 5,6 co-operative catalyst schemes, 7,8 and alternative support materials 9 that are capable of decreasing the CO bond strength of active sites, and ease its removal at lower potentials. Some progress has also been made in the development of electrocatalysts for the oxidation of C2+ alcohols like ethanol, 10,11 mainly through the use of Rh-based alloys that can facilitate C-C bond scission.…”
Section: Introductionmentioning
confidence: 99%
“…When used in electrocatalytic field, the performances of Pt nanozymes are strongly influenced by three main parameters, namely size/shape, coating, and surface properties [ 18 26 ]. While sizes in the range of few nanometers are necessary to mimic natural enzyme specificity and improve performance [ 27 30 ], shapes regulate the surface structure, i.e., the arrangement of the atoms at the surface [ 31 ] which has been demonstrated to strongly determine the surface properties of nanosized Pt in several applications including glucose oxidation [ 32 , 33 ]. As for the coating layer effect on Pt-based nanocatalysts, it has been reported that the surface coating can deteriorate the enzymatic properties of nanomaterials, posing a focus on nanoparticle synthetic protocols and subsequent modification [ 18 ].…”
Section: Introductionmentioning
confidence: 99%